2020
DOI: 10.12669/pjms.37.1.3655
|View full text |Cite
|
Sign up to set email alerts
|

ABO / Rh-D Blood types and susceptibility to Corona Virus Disease-19 in Peshawar, Pakistan

Abstract: Objectives: To determine the association between ABO/Rh-D blood types and susceptibility to SARS-CoV-2 infection in Pakistan. Methods: In this cross-sectional study, 1935 confirmed cases of COVID-19 were included using consecutive sampling. Age and gender-matched sample of 1935 blood donors was used as a comparison group. Chi-square test and binary logistic regression were used for inferential statistics. Results: Significantly higher proportion of blood type-B was observed in COVID-19 group (35.9%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 22 publications
5
19
1
1
Order By: Relevance
“…In populations where the B group distribution was higher than the other groups, situation also varied. In Pakistan, Rahim [9] reported a significant association between blood types B and AB and susceptibility to COVID-19. In Afghanistan, Saify [8] reported that being in the Ablood group remarkably increased the risk of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In populations where the B group distribution was higher than the other groups, situation also varied. In Pakistan, Rahim [9] reported a significant association between blood types B and AB and susceptibility to COVID-19. In Afghanistan, Saify [8] reported that being in the Ablood group remarkably increased the risk of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Rahim [ 9 ] reported that, in Pakistan, there was increased susceptibility among persons belonging to B and AB blood groups, and, in Pakistan, B blood group persons dominate (38%) over O and A blood group persons (29% and 23%, respectively) [ 13 ]. This also does not explain why the frequency of AB blood group infected patients increased.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the inclusion criteria, we excluded the 216 irrelevant studies by screening abstract and title. Eventually, a total of 22 articles (GÖKER et al, 2020;Hoiland et al, 2020;Ad'hiah et al, 2020;Solmaz and Araç, 2021;Taha et al, 2020;Dzik et al, 2020;Zalba et al, 2020;Chegni et al, 2020;Franchini et al, 2021;Gamal et al, 2021;Wu et al, 2020;Khalil et al, 2020;El-Shitany et al, 2021;Valenti et al, 2020;Muñiz-Diaz et al, 2021;Kibler et al, 2020;Barnkob et al, 2020;Bhandari et al, 2020;Rahim et al, 2021;Abdollahi et al, 2020;Fan et al, 2020;Boudin et al, 2020) were included in this systematic review and meta-analysis (Figure 1).…”
Section: Literature Searchmentioning
confidence: 99%